PENERAPAN EKONOMI HIJAU DALAM PEMBANGUNANBERKELANJUTAN: ANALISIS LITERATUR TEORITIS DAN EMPIRIS - Loso Judijanto; Al-Amin (JOURNAL OF COMMUNITY DEDICATION, 2024)
The application of the green economy in a development context is a paradigm that is gaining increasing attention to address global environmental challenges while promoting inclusive economic growth. Theoretical approaches highlight the potential for emissions reductions, resource efficiency, and a transition towards the use of renewable energy. Empirically, evidence shows that green economy policies can drive new job creation and reduce unemployment, positively impacting the economy and people's quality of life. Therefore, synergies between the government, private sector and communities are important in implementing green economy strategies. A shared commitment to sustainable practices can minimize social inequalities and ensure equitable access to resources and economic opportunities. Although challenges remain, the results of this study show that a green economy is a vital path to achieving sustainable development that is balanced with environmental preservation and social welfare.